Self-Esteem and Quality of Family Relationships in Children with Learning Disabilities - Mariana Sirotová; Zuzana Mičková; Krzysztof Rubacha (Nicolaus Copernicus University in Toruń, 2019)
The paper deals with the differences in the levels of self-esteem between children with learning disabilities and children with no learning disabilities and the differences in the assessment of the quality of relationships with parents between these two groups. The research was conducted on N= (60) pupils of higher school age, the group of children with learning disabilities N = (25) AM = (13.5), children without learning disabilities N = (35) AM = (13.8). The Rosenberg´s Self Esteem Scale constructed by the author was used to determine the levels of self-esteem in participating children while the Miglierini Personal Questionnaire, subscale of family relationships, was used to ascertain the family climate. The results indicate that both subgroups assess their relationships with parents positively, however a significant difference in the quality of relationships with parents can be found in favor of the group of children without learning disabilities. No differences between the groups were found in the levels of self-esteem.